Making sense of big questions that require multiple subjects: preliminary theorisation of an integrative philosophy of knowledge and empirical indications of a lack of subject connection within school curricula - Bowie, Robert A.; Aantjes, Rosanne; Woolley, Mary; Hulbert, Sabina; Revell, Lynn; Thomas, Caroline; Riordan, John-Paul (Journal of religious education, 2024)
This paper provides theorisation about a novel concept for education: an integrative philosophy of knowledge (IPK). This is proposed for school curricula to relate multiple subjects to big questions of personal and existential importance. Critical contemporary issues such as climate change education require multiple subject contributions but there is little clarity in the English education guidance on this drawing together, beyond the encouragement to do so in priority areas. Leading British thinkers have engaged the idea of the unity of knowledge, not without difficulty and criticism. The paper identifies reasons for a practical approach to consilience in school curricula. In addition to preliminary theorisation, in methodological ‘harmony’, this paper adds tentative empirical findings from a related research project that provides quantitative indications that such multi-subject connection is likely not happening. The findings are not definitive, but the perceptions of three groups of beginning and experienced teachers (secondary Religious Education (RE), secondary science and primary teachers) indicate that school curricula do not reflect an integrative approach to climate change education, and sex and relationships education, despite policy priority. A significant national survey could not detect many signs of connection. The paper speculates that RE could have a key epistemic role for the curriculum as a whole in this regard.